2003
DOI: 10.1098/rspb.2003.2402
|View full text |Cite
|
Sign up to set email alerts
|

Variable male potential rate of reproduction: high male mating capacity as an adaptation to parasite–induced excess of females?

Abstract: Numerous animals are known to harbour intracytoplasmic symbionts that gain transmission to a new host generation via female eggs and not male sperm. Bacteria of the genus Wolbachia are a typical example. They infect a large range of arthropod species and manipulate host reproduction in several ways. In terrestrial isopods (woodlice), Wolbachia are responsible for converting males into females (feminization (F)) in some species, or for infertility in certain host crosses in other species (cytoplasmic incompatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…However, there is evidence in feminizer-host systems for evolution of male reproductive behavior. In a comparative analysis, the male ability to fertilize multiple females was higher in two species carrying a feminizer than in five other species in which there was no feminizer present (Moreau and Rigaud 2003). This is consistent with the action of selection to partition ejaculates to enable a greater mating rate in males.…”
Section: Alteration In Mating System/reproductive Ecologysupporting
confidence: 65%
“…However, there is evidence in feminizer-host systems for evolution of male reproductive behavior. In a comparative analysis, the male ability to fertilize multiple females was higher in two species carrying a feminizer than in five other species in which there was no feminizer present (Moreau and Rigaud 2003). This is consistent with the action of selection to partition ejaculates to enable a greater mating rate in males.…”
Section: Alteration In Mating System/reproductive Ecologysupporting
confidence: 65%
“…With no fitness cost associated with Wolbachia and a strong symbiont transmission rate, the infection should spread deterministically in host populations (Taylor 1990). However, during Wolbachia spread, the population sex ratio becomes more and more femalebiased (Taylor 1990;Rigaud et al 1992), inducing: (i) the establishment of male mate choice, the males preferring uninfected females as mating partners (Moreau et al 2001); and (ii) increased opportunities for multiple copulations in males because of female-biased operational sex ratios (Moreau & Rigaud 2003). The uninfected females would therefore be more likely to receive the first mating, and the larger amount of sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Such events, although difficult to be observed, may occur in nature. On the other hand, populations that do persist take advantage of imperfect transmission of feminizing Wolbachia strains (Rigaud et al 1999b) or constrain the ability of Wolbachia to spread by exploiting the local scarcity of males (Moreau and Rigaud, 2003). Recent studies suggest that Wolbachia can also induce feminization in insect species as reported for the leafhopper Zyginidia pullula (Hemiptera: Cicadellidae) and the butterfly Eurema hecabe (Lepidoptera: Pieridae) (Negri et al 2006, Narita et al 2007.…”
Section: Wolbachia-induced Phenotypesmentioning
confidence: 99%